2021
DOI: 10.1007/s13300-021-01110-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with COVID-19 Hospitalization and Mortality: A Large Claims-Based Analysis Among People with Type 2 Diabetes Mellitus in the United States

Abstract: Introduction: Diabetes has been identified as a high-risk comorbidity for COVID-19 hospitalization. We evaluated additional risk factors for COVID-19 hospitalization and in-hospital mortality in a nationwide US database. Methods: This retrospective study utilized the UnitedHealth Group Clinical Discovery Database (January 1, 2019-July 15, 2020) containing de-identified nationwide administrative claims, SARS-CoV-2 laboratory test results, and COVID-19 inpatient admissions data. Logistic regression was used to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
(51 reference statements)
2
7
0
Order By: Relevance
“…Patients with type 2 diabetes using insulin had significantly higher odds of adverse events, which was expected, as insulin use is an indicator of an advanced stage of diabetes. This finding was consistent with other large studies 23–25. For instance, among 64 892 veterans with diabetes and COVID-19, insulin use was associated with higher odds of hospitalization and risk of death 25.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with type 2 diabetes using insulin had significantly higher odds of adverse events, which was expected, as insulin use is an indicator of an advanced stage of diabetes. This finding was consistent with other large studies 23–25. For instance, among 64 892 veterans with diabetes and COVID-19, insulin use was associated with higher odds of hospitalization and risk of death 25.…”
Section: Discussionsupporting
confidence: 91%
“…However, notably, iatrogenic hyperinsulinemia caused by exogenous insulin use might lead to adverse effects, including insulin resistance due to downregulation of insulin receptors, vascular changes, and subsequent adverse cardiovascular outcomes [96]. Moreover, our subgroup analyses as well as those from previous publications controlling for severity markers did not eliminate the association, raising concerns about the actual harmful effects of insulin [17]. Like DPP-4i, the increased risk of death among insulin users should be cautiously interpreted.…”
Section: Summary Of Main Findingsmentioning
confidence: 63%
“…Nonetheless, no data about metabolic control differences was given, and the authors only admitted that metformin use may reflect less advanced diabetes and fewer complications. Boye et al 48 analyzed 36,364 insured patients admitted for COVID-19 and concluded that metformin was associated with lower odds of hospitalization (OR 0.78; 95 % CI 0.71–0.86). In another study of ensured patients, Ghany et al 39 verified that metformin use was linked to a lower hospital admission (HR 0.71; 95 % CI 0.52–0.86; p = 0.01), but found no significant effect on the duration of hospitalization (median length of stay for metformin users was 11 days [IQR 5–46] and 14 days [IQR 6–30] for non-users; p = 0.5).…”
Section: Resultsmentioning
confidence: 99%